Targeting of NMDA Receptors in the Treatment of Major Depression - Dang, Yong-Hui; Ma, Xian-Cang; Zhang, Ji-Chun; Ren, Qian; Wu, Jin; Gao, Cheng-Ge; Hashimoto, Kenji (Current Pharmaceutical Design, 2014)
Major depressive disorder (MDD) is a common, recurrent mental illness that affects millions of people worldwide. Accumulating evidence suggests that the N-methyl-D-aspartate (NMDA) receptor, a subtype of glutamate receptors, plays an important role in the neurobiology and treatment of this disease. Currently, the non-competitive NMDA receptor antagonist ketamine is considered as one of the most attractive candidate drugs in therapy of treatment-resistant depression. A recent study demonstrated ketamine's rapid antidepressant activity in patients with treatment-resistant MDD and bipolar disorder. The response rate for ketamine ranged from 25% to 85% at 24 hours post-infusion and from 14% to 70% at 72 hours post-infusion, with generally mild adverse effects. Based on the role of the NMDA receptor in depression, a number of therapeutic drugs which interact with this receptor have been developed. In this article, we reviewed recent findings concerning the role of glutamatergic signaling in the neurobiology of MDD and potential, novel therapeutic drugs, such as ketamine, memantine, AZD6765, traxoprodil, MK-0657, GLYX-13, NRX-1047, D-cycloserine, sarcosine, all of which target this system.
Keywords: Depression